P-74 How implementing the foundation modules for productive ward has improved efficiency, safety and morale within the inpatient unit. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Pepper, Wendy; Griffiths, Dawn; Anderson, Kate; Nutting, Helen; Harris, Alison; Tudge, Karen; Gilfillan, Lynne; Perkins, Lynne
Abstract : Introduction: The inpatient unit has introduced the three foundation modules from the Productive Ward programme, Patient Status at a Glance, The Well Organised Ward and Knowing How we are Doing. The project commenced in 2014 and continues to develop. There have been significant changes in the way the Unit operates alongside increased staff morale, enthusiasm, ownership and pride in the environment and maintaining and improving standards Aims: The ultimate aim of the Productive Ward foundation modules is to release time to care by ensuring efficient systems are in place in a well organised environment Methods: A project lead planned and trained three groups to lead each module. Each group nominated a group lead who reported back to the project manager quarterly. Quarterly reports were included in the annual audit plan for Dorothy House. A ward vision was produced and clearly displayed outlining out core values. A project board was introduced to demonstrate progress and maintain momentum. Before and after photographs were taken to demonstrate improvements. Once an area was completed standards were set and regular audits commenced to ensure compliance and sustainability. Conclusions: Patient Status at a Glance: An electronic whiteboard has been introduced that informs handovers and MDT meetings. This can be accessed via the desk top for all clinical teams connected with IPU. It records a variety of patient information and has the ability to aid in reporting and audit Well Organised Ward: Each clinical area was assessed using the 5S tool involving to sort, set, shine, standardise and sustain. We worked with the three second rule where any item needed could be found within three seconds of entering the room. Knowing How we are Doing: Friends and family feedback, suggestion boxes and safety crosses were introduced. The safety crosses monitor any incidences or near misses related to pressure ulcers, falls or medication errors